Exome sequencing identifies truncating mutations in PRRT2 that cause paroxysmal kinesigenic dyskinesia - Chen, Wan-Jin; Lin, Yu; Xiong, Zhi-Qi; Wei, Wei; Ni, Wang; Tan, Guo-He; Guo, Shun-Ling; He, Jin; Chen, Ya-Fang; Zhang, Qi-Jie; Li, Hong-Fu; Lin, Yi; et al. (Nature genetics, 2011)
Zhi-Ying Wu and colleagues report the identification of truncating mutations in the PRRT2 gene in families with paroxysmal kinesigenic dyskinesia. PRRT2 encodes the proline-rich transmembrane protein 2. Paroxysmal kinesigenic dyskinesia is the most common type of paroxysmal movement disorder and is often misdiagnosed clinically as epilepsy. Using whole-exome sequencing followed by Sanger sequencing, we identified three truncating mutations within PRRT2 (NM_145239.2) in eight Han Chinese families with histories of paroxysmal kinesigenic dyskinesia: c.514_517delTCTG (p.Ser172Argfs*3) in one family, c.649dupC (p.Arg217Profs*8) in six families and c.972delA (p.Val325Serfs*12) in one family. These truncating mutations co-segregated exactly with the disease in these families and were not observed in 1,000 control subjects of matched ancestry. PRRT2 is a newly discovered gene consisting of four exons encoding the proline-rich transmembrane protein 2, which encompasses 340 amino acids and contains two predicted transmembrane domains. PRRT2 is highly expressed in the developing nervous system, and a truncating mutation alters the subcellular localization of the PRRT2 protein. The function of PRRT2 and its role in paroxysmal kinesigenic dyskinesia should be further investigated.